2017
DOI: 10.1111/jan.13482
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and variation of diabetes related symptoms, sleep disturbance and sleep‐related impairment in adults with type 2 diabetes

Abstract: Findings suggested that diabetes-related symptoms, including neuropathic pain and fatigue, are strongly related to sleep disturbance and sleep-related impairment in adults with type 2 diabetes, underscoring the need to include detailed assessments of neuropathic pain and fatigue when evaluating sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Similar results have been reported in a cross-sectional study among patients diagnosed with T2D, where patients reported higher levels of pain and fatigue that were closely related to sleep disturbance [ 15 ]. Another cross-sectional study reported that patients who were very active in their self-care related to T2D had lower depression, better social outcomes, and better physical function [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been reported in a cross-sectional study among patients diagnosed with T2D, where patients reported higher levels of pain and fatigue that were closely related to sleep disturbance [ 15 ]. Another cross-sectional study reported that patients who were very active in their self-care related to T2D had lower depression, better social outcomes, and better physical function [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…By the same token, sleep disorders (SD) have been shown to affect around 20-30% of the western population on a daily or weekly basis, leading to a lower quality of life [1]. These disorders have also been reported to be a risk factor for diseases such as diabetes, and they can encourage the presence of diabetes complications [1][2][3][4]. In fact, between 42-77% [3] of patients with type-2 diabetes mellitus (DM-2) are reported to suffer from sleep disorders, although few studies have analyzed their relationship with patient outcomes and quality of life [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, several studies have found a relationship between SD and neuropathic pain in patients with DM-2, highlighting the need to include detailed assessments of pain when exploring the SD of these patients [3]. The analysis of sensory phenotypes is a more frequently recommended strategy in patients with neuropathic pain because different phenotypes have been shown to reveal different neurobiological pain mechanisms [11,12], which could explain the heterogeneity of the patients [12] and the variability in clinical outcomes [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various T2D symptoms may explain the variation in sleep parameters including frequent nocturnal urination, hyperglycemia-related food consumption, hypoglycemia symptoms, obesity, pain, and distress [ 30 ]. A recent study showed that diabetes-related symptoms including neuropathic pain, diabetes distress, and depressive symptoms were more likely associated with sleep disturbances [ 31 ]. However, it is important to elucidate the additive effects of insomnia symptoms on sleep parameters in individuals with T2D.…”
Section: Introductionmentioning
confidence: 99%